(untitled) (Fiep Bulletin - online, 2016)
Introduction: Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative progressive disease, relatively rare and fatal, caused by a degeneration of the upper and lower motor neurons. Main symptoms of ALS are weakness, atrophy, fasciculation, cramps, spasticity, dysarthria, dysphagia and dyspnea. After the diagnosis, the condition takes from 3 to 5 years to present progressive incapacity resulting in respiratory insufficiency and death. In front of the interventions available, this condition requires a multidisciplinary teamwork, in order to promote better quality of life for the patients. Objective: Collect data from Brazilian literature about the physiotherapeutic motor treatment in patients with Amyotrophic Lateral Sclerosis – ALS. Method: Bibliographic research, realized between April and July of 2014, on Scielo and Lilacs databases, Capes periodic and Neurosciências Magazine, restricting the research to articles about motor physiotherapy published in Portuguese with no screening for year of publication. Results and Discussion: 851 articles were found in the databases, but only eight served the criterion of inclusion. The techniques more frequently reported were Hydrokinesiotherapy, Resisted exercises, Kinesiotherapy and Prospective Neuromuscular Facilitation. Conclusion: Motor physiotherapy in patients with ALS is being insufficiently reported in Brazilian literature. Investment in new studies in this area is needed because physiotherapy has an important role in the functional performance, actuating in different positive aspects aiming a better life quality for the patients.